Efek Timbal (Pb) Terhadap Pertumbuhan dan Adaptabilitas Acacia mangium Pada Tailing Emas - Bayu Winata; Basuki Wasis; Yadi Setiadi (Jurnal Silvikultur Tropika, 2019)
Gold mining is a human activity with high environmental risk through its tailing, due to the heavy metals content. Lead (Pb) is one of dangerous heavy metals in the world, because its toxicity to organism and environment. Phytoremediation is a method to remove hazard pollutant from environment by using plant. Acacia mangium is fast growing and pioneer tree species which mostly grow on the secondary forest as well as marginal land. Usually, this species is used for revegetation on postmining land. Study on Pb effect to A. mangium is an important issue to support phytoremediation advancement as well as for forest restoration. This study aimed to analyze the effect of Pb with several levels toward the growth and adptability of A. mangium on the gold tailing. The results showed that Pb increment on tailing were significantly effect on the growth and adaptability of the plants. A. mangium showed a well performance even on 900 mg Pb/kg tailing with high tolerance index (TI > 100%). Moreover, this species had ability to accumulate Pb in the root higher than shoot tissue. A. mangium had a good potency as phitoremediant plant, also as revegetation plant on the marginal land, such as on the gold mining tailing. Key words: Acacia mangium, heavy metal, lead, phytoremediation, Pb